2018
DOI: 10.1021/acscatal.8b00393
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Control in the Catalytic Insertion Polymerization of Norbornenes as Rationale for the Lack of Reactivity of Endo-Substituted Norbornenes

Abstract: The catalytic insertion polymerization of substituted norbornenes (NBEs) leads to the formation of a family of polymers which combine extreme thermomechanical properties as well as unique optical and electronic properties. However, this reaction is marred by the lack of reactivity of endo substituted monomers. It has long been assumed that these monomers chelate the metallic catalyst, leading to species which are inactive in polymerization. Here we examine the polymerization of cis-5-norbornene-2,3-dicarboxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…The second reason is the used DCPD was enriched by a less reactive endo ‐isomer, while HexNB consisted of approximately equal amounts of exo ‐ and endo ‐isomers. Thus it was shown that in addition polymerization of norbornenes, exo ‐derivatives as a rule are more reactive than endo ‐isomers . The last reason is the capability of DCPD to form stable chelates with the catalyst active species ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second reason is the used DCPD was enriched by a less reactive endo ‐isomer, while HexNB consisted of approximately equal amounts of exo ‐ and endo ‐isomers. Thus it was shown that in addition polymerization of norbornenes, exo ‐derivatives as a rule are more reactive than endo ‐isomers . The last reason is the capability of DCPD to form stable chelates with the catalyst active species ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus it was shown that in addition polymerization of norbornenes, exo-derivatives as a rule are more reactive than endo-isomers. [44,45] The last reason is the capability of DCPD to form stable chelates with the catalyst active species (Figure 7). Thus, the presence of the second double bond in DCPD leads to the possibility to coordinate with Pd-centers in different ways (Figure 7, structures I-III) and there is a competition between these double bonds for the vacant coordination place at Pd-complexes.…”
Section: Addition Copolymerization Of Dicyclopentadiene and 5-n-hexylmentioning
confidence: 99%
“…As for many other substituted norbornenes, the endo isomer (the major one) is the least reactive. [10][11][12] Also, both endocyclic and exocyclic unsaturations in endo-VNB are perfectly arranged to coordinate to the metal in a chelating fashion, which could slow down the polymerization process. Even in a monodentate fashion the terminal double bond in VNB is a competing ligand.…”
Section: Introductionmentioning
confidence: 99%
“…The Diels‐Alder reactions between cyclopentadiene with dienophiles readily produce a variety of functionalized NBs with predominant formation of the endo ‐isomers. Generally, the exo ‐isomers show the higher polymerizability than the endo ‐isomers, which is believed to be due to steric hindrance of an endo ‐substituent and/or chelation of a terminal transition metal with an endo ‐substituent 8–11 . Addition polymerizations of 5‐norbornene‐2‐carboxylic acid esters, ones of the most investigated functionalized NBs, have been performed by using less oxophilic but highly active Pd catalysts, including [( η 3 ‐allyl)PdL 2 ]SbF 6 (L = solvent), 10,12 ( t Bu 3 P)Pd(Me)Cl, 13,14 [( η 3 ‐allyl)Pd(NHC)Cl] (NHC = N‐heterocyclic carbene), 15 Pd(acac) 2 , 16 Pd(dba) 2 (dba = dibenzylideneacetone), 17 and Pd(acac)(MeCN) 2 BF 4 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the exo-isomers show the higher polymerizability than the endo-isomers, which is believed to be due to steric hindrance of an endo-substituent and/or chelation of a terminal transition metal with an endo-substituent. [8][9][10][11] Addition polymerizations of 5-norbornene-2-carboxylic acid esters, ones of the most investigated functionalized NBs, have been performed by using less oxophilic but highly active Pd catalysts, including [(η 3 -allyl)PdL 2 ]SbF 6 (L = solvent), 10,12 ( t Bu 3 P)Pd(Me)Cl, 13,14 [(η 3 -allyl)Pd(NHC)Cl] (NHC = N-heterocyclic carbene), 15 Pd(acac) 2 , 16 Pd(dba) 2 (dba = dibenzylideneacetone), 17 and Pd(acac)(MeCN) 2 BF 4 . 18 Living polymerization was also performed by using a catalytic system of ( t Bu 3 P)Pd(Me)Cl/NaB[3,5-(CF 3 ) 2 C 6 H 3 ] 4 .…”
Section: Introductionmentioning
confidence: 99%